2008
DOI: 10.1002/clen.200700042
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Crude Oil by Individual Bacterial Strains and a Mixed Bacterial Consortium Isolated from Hydrocarbon Contaminated Areas

Abstract: A preliminary study was undertaken to determine the optimal conditions for the biodegradation of a crude oil. Among 57 oil-degrading bacterial cultures isolated from oil-contaminated soil samples, Bacillus sp. IOS1-7, Corynebacterium sp. BPS2-6, Pseudomonas sp. HPS2-5, and Pseudomonas sp. BPS1-8 were selected for the study based on the efficiency of crude oil utilization. Along with the selected individual strains, a mixed bacterial consortium prepared using the above strains was also used for degradation stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
82
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(104 citation statements)
references
References 36 publications
10
82
0
2
Order By: Relevance
“…Thus, providing an optimum pH condition between pH 6-8.5 is supportive to bacterial population, and therefore, it is supporting the biodegradation process. Satishkumar et al (2008) found that pH ranging between 7 and 8 was more favorable for all the bacterial isolates and mixed bacterial consortium for degradation of crude oil. Similarly, Salmon et al (1998) reported that pH 7 was the optimum pH for degradation of hydrocarbon.…”
Section: Effect Of Npk and Bulking Agents On Enzyme Inductionmentioning
confidence: 95%
“…Thus, providing an optimum pH condition between pH 6-8.5 is supportive to bacterial population, and therefore, it is supporting the biodegradation process. Satishkumar et al (2008) found that pH ranging between 7 and 8 was more favorable for all the bacterial isolates and mixed bacterial consortium for degradation of crude oil. Similarly, Salmon et al (1998) reported that pH 7 was the optimum pH for degradation of hydrocarbon.…”
Section: Effect Of Npk and Bulking Agents On Enzyme Inductionmentioning
confidence: 95%
“…The indigenous bacterial consortium consisting of three bacterial isolates was selected. The crude oil-degrading efficiency (qualitative and quantitative) of individual bacterial isolates Pseudomonas strains (PSI, PSII, PSIII) was screened on minimal salt medium as described elsewhere [9], using crude oil as the sole carbon and energy source [10]. These selected isolates were characterized and identified using biochemical tests and 16S rRNA sequencing from The Energy and Resources Institute (TERI) New Delhi, India.…”
Section: Source Of Bacterial Consortiummentioning
confidence: 99%
“…Microbial degradation can be accomplished by different species of microorganisms that are both native to the soil and added as effective degrading strains. The microbial degradation is generally higher than 40% within 1 year of disposal and may be as high as 70% in some cases (Sathishkumar et al, 2008). Influencing factors for microbial remediation include soil moisture content, soil temperature, soil pH, oxygen supply, nutrients, oxidation-reduction potential, soil texture and soil structure (Riser-Roberts, 1998).…”
Section: Introductionmentioning
confidence: 99%